Tanfidzu Ta'limil Lughoh Al-arabiyah Bi istikhdami Kitabi Al-Lughoh Al-Arabiyah Li Aghradi Al-Khosoh - Amira Sa’idah, Mandrasi; Ruchamain, Tsaniya; Syamsul Arifin, Muhammad (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2022)
Purpose- The research purposed to describe and elaborate Arabic teaching learning process using Arabic textbook for special purposes for university level.  Design/Metodology/Approach- This study is a field study, a kind of descriptive-qualitative in which the technique of data collection used observation, interview and written documentation and for data analysis it used interactive analysis of Miles and Huberman.  Findings- The research resulted that the process of Arabic teaching learning using a textbook for special purposes in nutrition science was conducted with a focus on listening and speaking skills throughout audio-visual method. The steps of teaching: First, a preface where the teacher explains the topic related to new material. Second, instruction activities that begins with teaching vocabularies, Arabic listening about nutrition, interactive question-answer and speaking and vocabularies test. Third, Evaluation by giving homework then closing.    Research Limitation/Implications- The limitation of the problem in this research is focused on teaching Arabic on speaking and listening skills, and has not discussed teaching on other skills, namely the ability to write and read. However, this study explains the teaching of Arabic, especially to students of the Nutrition Study Program, which is equipped with materials and exercises related for nutrition science students using special textbook that has been designed for university level  Keywords: Arabic Teaching, Arabic Textbook for Special Purposes, Nutrition Science